Emotional intelligence and decision making among employees at Kolej Yayasan Sabah / Maslienda Abd. Ghani - Abd. Ghani, Maslienda (2008)
The competition in today's business environments requires organizations to hire employees with high Emotional Intelligence (El) and good decision making. Even though Intellectual Intelligence (IQ) may be important for employees, it does not always guarantee that they have sufficient level of Emotional intelligence which is required in making decision. With the self-administration of 120 questionnaires to all employees at Kolej Yayasan Sabah, the study examined the Emotional Intelligence and their decision making. Besides, the study also determined the relationship between Emotional Intelligence and decision making as well as gender differences on Emotional Intelligence. The result of this study revealed that one's decision making is influenced by emotional intelligence's elements; self-awareness, self-regulation, motivation, empathy, and social skills. It was also found that gender does not have significant correlation with one's Emotional Intelligence. Thus, it is recommended that the organizations should develop training programs to enhance their employees' emotional sensitivity and makinga good decision. On top of that, it is also recommended for this organization to do an ongoing effort to build skills in Emotional Intelligence throughout the organization through the assessment on the each individual.